EU (NÃO) SOU DA SUA RUA: Análise arqueológica dos discursos jurídicos sobre a cidade no “Caso Edifício Santa Luzia” em São Luís (MA) - TAVARES, Regina Lúcia Gonçalves (2017)
The legal and political instruments for democratization of the city and the access to the right to housing are closely linked to the right to the city, which in the case of Brazil is normatively shaped by constitutional and infra-constitutional provisions that provide for and legitimize urban policy practices, strictly speaking, should prioritize the social functionalization of property and the city. However, when confronted with the country's large housing deficit, especially in the urban environment, such precepts are capable of revealing the growing social inequality that exacerbates the inefficiency of the positive norm, leaving it to be expected that other factors act and challenge the logic of the law, making it prevail a reality far removed from a sustainable city model foreseen in the abstract rule. This initial finding is what challenges the present research that, in the wake of a judicial occupation’s study, carried out by 33 low-income families, in an abandoned residential building, built in a central area of the city of São Luís (MA), search for findings that, led by an archaeological analysis of the legal discourses supported in that process, allow to investigate to what extent the statements produced by the institutions of the justice system, in order to solve the problem of housing at risk, are influenced by other urbanistic knowledge to the formulation of their discourses and, thus, to ratify a prevailing model of segregatory urbanization. Applying the method of archaeological analysis of Michel Foucault's discourse, a bibliographical review began a mapping of the urban schools that influenced the urban policies and the cities’s forms of organization throughout the 20th century, taken, in accordance with the foucaultian language, as an archaeological event. Then, came the systematic exposition of the normative set corresponding to the matter, on which rules and principles were worked in the light of a dworkian conception of justice and the Robert Alexy’s theory of undamental rights. In the possession of the bibliographical research’s data, then, they could serve as a buffer for the analysis of the legal discourses emitted in the case of the studied urban occupation. The results showed that legal discourses, chaeologically taken as discursive events, are extremely affected by the non-discursive practices of a conventional urban epistemology, able to constrain them to the point where they have a strong influence on the formulation of truths about a social model and economically unsustainable urban policy.